High levels of CC‐chemokine expression and downregulated levels of CCR5 during HIV‐1/HTLV‐1 and HIV‐1/HTLV‐2 coinfections. Issue 5 (10th February 2015) - Oo, Z.; Barrios, C.S.; Castillo, L.; Beilke, M.A.
<x xml:space="preserve">Abstract</x> The human T‐cell lymphotropic virus type 1 (HTLV‐1) and HTLV‐2 are common copathogens among Human Immunodeficiency Virus (HIV)‐infected individuals. HTLV‐2 may confer a survival benefit among patients with HIV‐1/HTLV‐2 coinfections, along with lower plasma HIV‐1 levels and delayed rates of CD4+ T‐cell decline. These effects have been attributed to the ability of the HTLV‐2 viral transactivating Tax2 protein to induce the production of high levels of antiviral CC‐chemokines and to downregulate expression of the CCR5 receptor, resulting in impaired entry of HIV‐1 into CD4+ T‐cells. This study investigated the innate immunity of coinfected HIV/HTLV individuals by testing the ability of patient PBMCs to produce CC‐chemokines in association CCR5 receptor modulation. The cellular proliferative responses of HIV/HTLV coinfected versus HIV monoinfected individuals were also evaluated. Higher levels of MIP‐1α, MIP‐1β, and RANTES (P < 0.05) were found in HIV‐1/HTLV‐2 coinfected group compared to HIV‐1 monoinfected population. Upregulated levels of RANTES were shown in HIV‐1/HTLV‐1 after 1 and 3 days of culture (P < 0.05). Lymphocytes from HIV‐1/HTLV‐2 coinfected individuals showed significant CCR5 downregulation after 1 and 3 days of culture compared to lymphocytes from HIV‐1 and uninfected groups (P < 0.05). Lower percentages of CCR5‐positive cells were found in HIV‐1/HTLV‐1 coinfected after 3 days of incubation (P < 0.05). Levels of proliferation were significantly higher in the HIV‐1/HTLV‐1 group compared to HIV‐1 alone (P < 0.05). HTLV‐2 and HTLV‐1 infections may induce the involvement of innate immunity against HIV‐1 via stimulation of CC‐chemokines and receptors, potentially modifying CCR5/HIV‐1 binding and HIV‐1 progression in coinfected individuals. J. Med. Virol. 87:790–797, 2015. © 2015 Wiley Periodicals, Inc.